Review of Electronic Medical Record Data Processing To Support Quality Re-porting Activities At The Medical Records Installation Of Umar Wira-hadikusumah Regional Hospital - Oktafia Akbar Putri; Neni Rohaeni (International Journal of Health and Pharmaceutical (IJHP), 2026)
Electronic Medical Records play a vital role in providing accurate and complete data to support hospital quality reporting. However, incomplete medical record entries remain a barrier to producing optimal quality reports. This study aims to review the processing of Electronic Medical Record data to support quality reporting activities at the Medical Record Installation of Umar Wirahadikusumah Regional General Hospital. The study used a quantitative method with a descriptive approach. The study population consisted of 128 Electronic Medical Record data from inpatients for the period of December 2025, and the entire population was sampled using a total sampling technique. Data collection was carried out through observation, structured interviews, and a medical record completeness checklist. Data were analyzed descriptively. The results showed that Electronic Medical Record data processing had been carried out through the stages of sampling, data collection, data processing, and presentation of quality reports. The level of completeness of medical records reached 75% (96 files), while 25% (32 files) were still incomplete, especially in diagnosis, patient identity, service forms, and authentication. This study concludes that the Electronic Medical Record data processing process has supported quality reporting, however, increasing compliance in filling out medical records through continuous monitoring and evaluation is still needed to improve data quality and hospital quality reporting.